FUNGSI UANG DALAM PERSPEKTIF EKONOMI ISLAM - Aswawi, Nurafia (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
This research aims to determine how consumption behavior should be according to the Islamic Economic perspective. This research is a type of literature research that focuses on discussing how Islam regulates the use of money in the economic system. Based on the result of the analysis it can be concluded that; 1) There are only 2 functions of money in the perspective Islamic economics, namely; (a) money as unit of account and (b) money as medium of exchange. 2) There are 4 functions of money in the conventional economic prespective, namely; (a) money as unit of account, (b) money as medium of exchange, (c) money as store of value, (d) money as standard of deffered payment. 3) In a conventional economic system, money functions not only as a legal medium of exchange but also as a commodity. Whereas in the Islamic economic system, money is only a meium of exchange and not a commodity that is traded.